Varieties Of Science Learning Assessment In 21st Century Learning: A Systematic Literature Review - Fitria, Yanti; Ayani, Nabilah Ikrimah (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
This review identifies and analyzes the varieties of science learning assessment applied in 21st-century science education. Despite the growing emphasis on scientific literacy and higher-order thinking, few studies have systematically mapped diverse assessment forms aligned with 21st-century competencies. To address this gap, a Systematic Literature Review (SLR) was conducted on peer-reviewed articles published between 2015 and 2025 using the Scopus, ScienceDirect, SpringerLink, ERIC, and Google Scholar databases. Twenty-seven studies meeting the inclusion criteria were analyzed thematically.The review reveals five dominant assessment categories: authentic assessment, competency-based assessment, digital and technology- enhanced assessment, formative and reflective assessment, and collaborative assessment. These assessment approaches indicate a shift from traditional test-based evaluation toward assessing scientific reasoning, creativity, collaboration, and contextual problem-solving. The findings highlight that modern science assessment emphasizes process-oriented evaluation and the integration of digital tools to support adaptive feedback and learning analytics. This review contributes a comprehensive synthesis of assessment innovations in science education and underscores the need for holistic, technology-integrated evaluation practices. Strengthening teacher capacity in designing innovative assessments and conducting empirical studies on their classroom effectiveness is recommended for advancing science education in the digital era.